Enhanced Fuzzy-Power Control for WECS based on Variable Wind Speed-Driven DFIG Using SVM Strategy under Sub- and Super-synchronous Operating Modes - Amrane, Fayssal; Itouchene, Hichem (Periodica polytechnica. Electrical engineering and computer science, 2025)
This paper presents an efficient stator power control algorithm for a grid-connection wind turbine system based on a doubly fed induction generator (DFIG) operating under variable wind speed conditions. The proposed approach focuses on controlling the stator power of the DFIG under varying operating conditions. In order to extract maximize wind power extraction, the stator-side power factor is maintained at unity through maximum power point tracking (MPPT). An advanced fuzzy-type controller, known as Type-2 Fuzzy logic control (T2-FLC), is proposed to regulate the rotor's direct and quadrature currents. Simulation results obtained in the MATLAB/Simulink environment demonstrate that the T2-FLC controller offers robust performance, superior dynamic response, and enhanced operational efficiency for the wind energy and drive applications in steady-states conditions.